The spontaneity of social network: a possibility for re-enchanting network study?. Issue 6 (7th October 2014) - Accard, Philippe; Assens, Christophe
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – For current works, agents create social network by drawing on the knowledge of their immediate environment, and they use network for cooperating with one another and for promoting their own economic and social interests. The purpose of this paper is to aid in re-enchanting network study, and present network as spontaneous social construction. Design/methodology/approach – The paper draws on Hayek's spontaneous order. For Hayek, agents have access to a wide knowledge about social system, and use this knowledge to spontaneously coordinate with each other in the pursuit of their self-interests. Findings – The authors develop the idea by presenting and performing an analogy of Hayek's spontaneous order to emergent structures. The result of this analogy is a conception of network dynamics wherein the spontaneous social construction of network structures is achieved by agents who have knowledge of the interaction rules that guide structures production, and who, by drawing on this knowledge, are able to influence the emergence of network structures. Agents thus spontaneously contribute to the emergence of a network, to its growth, and its decline. Originality/value – This new conception of network focusses on the processes of the social construction of network structures. It provides a better account of network change and development than current works, and because it stresses the spontaneous, fragile and ephemeral character of network, it can prove useful for the re-enchantment of network studies.